2014 14th UK Workshop on Computational Intelligence (UKCI) 2014
DOI: 10.1109/ukci.2014.6930152
|View full text |Cite
|
Sign up to set email alerts
|

Evolution-in-materio: Solving function optimization problems using materials

Abstract: Abstract-Evolution-in-materio (EIM) is a method that uses artificial evolution to exploit properties of materials to solve computational problems without requiring a detailed understanding of such properties. In this paper, we show that using a purpose-built hardware platform called Mecobo, it is possible to evolve voltages and signals applied to physical materials to solve computational problems. We demonstrate for the first time that this methodology can be applied to function optimization. We evaluate the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…In other work using Mecobo it has been shown that digital logic functions can be implemented [9]. We have also obtaining encouraging results on function optimization [13], bin packing, traveling salesman [4] and machine learning classification [14] problems. In principle, some evolved systems could act as standalone devices.…”
Section: Conclusion and Future Outlookmentioning
confidence: 57%
See 1 more Smart Citation
“…In other work using Mecobo it has been shown that digital logic functions can be implemented [9]. We have also obtaining encouraging results on function optimization [13], bin packing, traveling salesman [4] and machine learning classification [14] problems. In principle, some evolved systems could act as standalone devices.…”
Section: Conclusion and Future Outlookmentioning
confidence: 57%
“…The remaining members of the population are formed by mutating the parent. This algorithm was used partly because of its simplicity and partly because in other studies comparisons have been made between an evolutionary software approach and evolution-in-materio [4], [14], [13].…”
Section: Methodsmentioning
confidence: 99%
“…The platform is in use by several researchers in the Nascense project consortium, e.g. University of York [13] for function optimization.…”
Section: Discussionmentioning
confidence: 99%
“…Function Optimisation a. This has no inputs and as many outputs as there are dimensions in the function to be optimised [41,42] 5. Bin-Packing a.…”
Section: Travelling Salesmanmentioning
confidence: 99%